Knowledge, Attitude and At-Risk Behaviour for Heart Diseases among Secondary School Teachers in Ibadan Metropolis - Familoni IF; Moronkola OA; Familoni OB (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: Cardiovascular diseases remain the leading cause of death in developed countries, becoming prevalent in the developing world. Risk behaviour may result in unfavourable outcomes in cardiovascular diseases. Secondary school teachers constitute a large cohort of educated middle-level income earners who can influence young and upcoming individuals due to their profession. Objective: To assess the knowledge, attitude and at-risk behaviour for heart diseases among secondary school teachers in Ibadan Metropolis. Methods: A cross-sectional research design was used. Self- developed, field pre-tested questionnaire was employed to collect the relevant data from 200 randomly teachers. Cronbach alpha method was used to test the internal consistency of the test instruments and a measure of its scale in reliability. Results: The study population comprised 39.0% males and 61.0% females. Most of the respondents (58.5%) were over 40 years, with an overall mean age of 40.2±3.1 years. The knowledge of secondary school teachers about heart diseases was poor (47.8%), while attitude and at-risk behaviours were unsatisfactory (weighted means 2.34 and 2.23 respectively against a criterion of 2.5). Conclusion: The secondary school teachers in Ibadan Metropolis had poor knowledge of heart diseases and demonstrated poor attitude and unsatisfactory at-risk behaviour about the diseases.